Thermolability of mutant MMACHC protein in the vitamin B12-responsive cblC disorder. - Froese, D; Healy, S; McDonald, M; Kochan, G; Oppermann, U; Niesen, F; Gravel, R (2010)
Methylmalonic aciduria and homocystinuria, cblC type, is the most common inborn error of cellular vitamin B12 metabolism. We previously showed that the protein carrying the mutation responsible for late-onset cblC (MMACHC-R161Q), treatable with high dose OHCbl, is able to bind OHCbl with wild-type affinity, leaving undetermined the disease mechanism involved [Froese et al., Mechanism of responsiveness, Mol. Genet. Metab. (2009).]. To assess whether the mutation renders the protein unstable, we investigated the thermostability of the wild-type and mutant MMACHC proteins, either unbound or bound to different cobalamins (Cbl), using differential scanning fluorimetry. We found that MMACHC-wt and MMACHC-R161Q are both very thermolabile proteins in their apo forms, with melting temperatures (T(m)) of 39.3+/-1.0 and 37.1+/-0.7 degrees C, respectively; a difference confirmed by unfolding of MMACHC-R161Q but not MMACHC-wt by isothermal denaturation at 35 degrees C over 120 min. However, with the addition of OHCbl, MMACHC-wt becomes significantly stabilized (Delta T(m max)=8 degrees C, half-maximal effective ligand concentration, AC(50)=3 microM). We surveyed the effect of different cobalamins on the stabilization of the wild-type protein and found that AdoCbl was the most stabilizing, exerting a maximum increase in T(m) of approximately 16 degrees C, followed by MeCbl at approximately 13 degrees C, each evaluated at 50 microM cofactor. The other cobalamins stabilized in the order (CN)(2)Cbi>OHCbl>CNCbl. Interestingly, the AC(50)'s for AdoCbl, MeCbl, (CN)(2)Cbi and OHCbl were similar and ranged from 1-3 microM, which compares well with the K(d) of 6 microM for OHCbl [Froese et al., Mechanism of responsiveness, Mol. Genet. Metab. (2009).]. Unlike MMACHC-wt, the mutant protein MMACHC-R161Q is only moderately stabilized by OHCbl (Delta T(m max)=4 degrees C). The dose-response curve also shows a lower effectivity of OHCbl with respect to stabilization, with an AC(50) of 7 microM. MMACHC-R161Q showed the same order of stabilization as MMACHC-wt, but each cobalamin stabilized this mutant protein less than its wild-type counterpart. Additionally, MMACHC-R161Q had a higher AC(50) for each cobalamin form compared to MMACHC-wt. Finally, we show that MMACHC-R161Q is able to support the base-off transition for AdoCbl and CNCbl, indicating this mutant is not blocked in that respect. Taken together, our results suggest that protein stability, as well as propensity for ligand-induced stabilization, contributes to the disease mechanism in late-onset cblC disorder. Our results underscore the importance of cofactor stabilization of MMACHC and suggest that even small increases in the concentration of cobalamin complexed with MMACHC may have therapeutic benefit in children with the late-onset, vitamin responsive cblC disease.